2015
DOI: 10.1097/jcn.0000000000000137
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Actions During the Decision Making Process Among Men With a First Acute Myocardial Infarction

Abstract: Healthcare professionals should be aware that men experience a range of insidious and vague symptoms during their first AMI and must give greater emphasis to their narratives, particularly when objective clinical signs are limited or absent. Consideration should be given to the ways laypeople interpret online information when designing healthcare resources for the Internet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The participants in these studies also performed different self-care activities to manage the symptoms before care-seeking. 42 , 43 Many of the findings in our study are similar with these results and with results from several other studies on care-seeking processes in MI patients. 10 15 , 17 21 We can therefore assume that the process of care-seeking for MI in people with diabetes is similar to that for those without diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…The participants in these studies also performed different self-care activities to manage the symptoms before care-seeking. 42 , 43 Many of the findings in our study are similar with these results and with results from several other studies on care-seeking processes in MI patients. 10 15 , 17 21 We can therefore assume that the process of care-seeking for MI in people with diabetes is similar to that for those without diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…Absence of chest pain in AMI is more common in patients with a history of diabetes, in women, older patients6 7 and in patients with non ST-segment-elevation myocardial infarction (non-STEMI) 8. Patients with AMI with insidious, vague or atypical symptoms have difficulties in interpreting and acknowledging bodily symptoms 9–12. Moreover, atypical symptoms of AMI are associated with significantly higher mortality5 13–15 for reasons that are not entirely clear.…”
Section: Introductionmentioning
confidence: 99%
“…Another study developed in Sweden, with 21 infarcted men, also found that the delay in seeking specialized medical care was associated with misinterpretation of symptoms, illusion of invulnerability, a belief that symptoms would disappear or attempt to relieve or treat symptoms before seeking specialized care (19) .…”
Section: Discussionmentioning
confidence: 96%